Laproendoscopic single site oesophageal diverticulectomy - Palanivelu, Chinnusamy (Medknow Publications & Media Pvt Ltd, 2013)
Epiphrenic divericula are uncommon disorders of the lower oesophagus, which are symptomatic in only 15–20% of cases. The optimum treatment modality for such cases remains an oesophageal diverticulectomy with long myotomy with or without an antireflux operation. Recently, this is increasingly being done through the laparoscopic approach. Here we describe the first reported case of oesophageal diverticulectomy through the laparoendoscopic single site approach. A 57-year-old man presented to us with 6 months history of dysphagia and regurgitation. Patient was investigated with upper gastrointestinal (UGI) endoscopy, barium swallow, CECT chest and abdomen, oesophageal manometry and 24 hour pH study. He was diagnosed to have lower oesophageal diverticulum with mildly elevated pressure readings in manometric studies with normal peristalsis. Based on his symptoms, he was taken up for surgery. A laparoscopic transhiatal oesophageal diverticulectomy with myotomy was done through laparoendoscopic single site technique. The procedure lasted 160 min. There was no intraoperative complication. Gastrograffin study was done on postoperative day 2 following which he was started on liquids. He made an uneventful recovery and was discharged on fourth day. He remained asymptomatic on follow up. Oesophageal diverticulectomy is possible through laparoendoscopic single site approach if necessary expertise is available.